Role of echocardiography in uncomplicated Staphylococcus aureus catheter-related bloodstream infections. Issue 18 (7th May 2021) - Mun, Seok Jun; Kim, Si-Ho; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; Peck, Kyong Ran
Abstract : Abstract: Uncomplicated bacteremia and catheter-related bloodstream infection (CRBSI) are frequently suggested as factors associated with low risk of infective endocarditis in Staphylococcus aureus bacteremia (SAB). Nevertheless, guidelines recommend that echocardiography in all patients with SAB. We evaluated the effects of echocardiography on patient outcomes. Patients with uncomplicated S. aureus CRBSI were retrospectively identified between January 2013 and June 2018 at a 1950-bed, tertiary-care university hospital. Treatment failure was defined as any case of relapse or all-cause death within 90 days. Of 890 SAB patients, 95 with uncomplicated S. aureus CRBSI were included. Thirty-two patients underwent echocardiography within 30 days of their first positive blood culture. Two patients who underwent echocardiography revealed right-sided infective endocarditis. One patient who did not undergo echocardiography experienced recurrent SAB (peripheral CRBSI) 85 days after his first positive blood culture. There were no SAB-related deaths. The Kaplan–Meier curves of treatment failure showed no significant differences between patients who did and did not undergo echocardiography ( P  = .77). In multivariable analysis, risk factors for treatment failure were liver cirrhosis (hazard ratio: 9.60; 95% confidence interval: 2.13–43.33; P  = .003) and other prostheses (hazard ratio: 63.79; 95% confidence interval: 5.05–805.40; P  = .001). This study did not verify the putative association between treatment failure and implementation of echocardiography in patients with uncomplicated S. aureus CRBSI. Given the low observed rates of adverse outcomes, routine echocardiography might not be obligatory and could be performed on an individual basis. Abstract : Supplemental Digital Content is available in the text